RETRACTION NOTICE 2 - Różalski , Antoni; Krajewska , Wanda M.; Mielczarek, Mariusz (Acta Archaeologica Lodziensia, 2023)
This notice refers to: "ARTICLE RETRACTED DUE TO PLAGIARISM: Bronze coins in the Roman provinces on the Lower Danube in the middle of the 3rd century. Studies on coin circulation". We, the Publisher and Editor-in-Chief of "Acta Archaeologica Lodziensia" have retracted the following article: Rakoczy Jacek. 2015. Bronze coins in the Roman provinces on the Lower Danube in the middle of the 3rd century. Studies on coin circulation, "Acta Archaeologica Lodziensia", 61, 49-61. Since publication, it has come to our attention that substantial parts of the paper are plagiarism of Cristian Gazdac's work entitled Monetary circulation in Dacia and the provinces from the Middle and Lower Danube from Trajan to Constantine I (AD 106-337) published in 2010 by MEGA Publishing House. The author has been informed about the retraction of the article. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’. October 9th, 2023 ADDENDUM The original source of plagiarism of the article indicated in the retraction notice is the article by Cristian Găzdac entitled Aspects of coin circulation in Roman Dacia published in a monograph "Roman Coins Outside the Empire. Ways and Phases, Contexts and Functions. Proceedings of the ESF/SCH Exploratory Workshop, Radziwill Palace, Nieborow (Poland), 3-6 September 2005", Moneta 84, Wetteren 2008, pp. 269-294. December 5th, 2023